A comparison of conventional and grid techniques for chest radiography in field surveys. Issue 4 (October 1973) - Washington, J. S.; Dick, J. A.; Jacobsen, M.; Prentice, W. M.
Abstract : Washington, J. S., Dick, J. A., Jacobsen, M., and Prentice, W. M. (1973). British Journal of Industrial Medicine, 30, 365-374. A comparison of conventional and grid techniques for chest radiography in field surveys. The effect on the quality of chest radiographs using a reciprocating grid with a moderately high kilovoltage (96 to 105 kV) has been studied. A total of 1 710 mineworkers had two postero-anterior chest radiographs taken at the same visit to a linked pair of mobile ϰ-ray units. One film was taken with conventional exposure factors and the other with moderately high kilovoltage and a reciprocating grid. The grid was exchanged between the two units according to a randomized plan so that the first radiograph was not always taken with the same technique. The 3 420 films so produced were subsequently assessed for quality by five doctors experienced in reading chest films. The films were examined singly in random order and the reader did not know which technique had been used for a given film. Four of the readers recorded improved quality using the grid technique for films from men whose antero-posterior chest measurements exceeded 254 mm (10 in), but they preferred the conventional exposure technique for films from men whose chest measurements were less than 254 mm. Results from all film pairs where a difference in quality was recorded showed no overall advantage for either technique.